Keanekaragaman dalam al-Qur’an - Muhammad Chirzin (TSAQAFAH, 2011)
The diversity of race, language, class, and culture is a wealth; basically, it is a beautiful gift in this life. However, the reality is precesely the social conflict among the society. This article explores the issue of diversity contained in al Qur’an. Some of the key themes included: diversity as sunnatullah, diversity in unity, religious and ethnic diversity, and diversity of professions. Al Qur’an has mentioned several groups of religious believers and provided guidance association order among religious believers. Religious diversity certainly makes Muslim necessitates acknowledging and respecting other religion save Islam. Al Qur’an has mentioned also a variety of occupations based on interests, talents, expertise, and particular skills. The fragmentation and understanding diversity have caused by egoism and truth claiming of each group and individual, but no one has knowledge covering everything from different sides or corners. Above all knowledge is the Almighty owner off all knowledge. With feeling most true someone or group tends to feel the best and have the right to insult any others. That is the base of the dispute and spiritual decline. Mukmin has to preserve the noble character in association, and keep away from bad manner. Among mukmin must love each other and maintain good manners. Finally, this study is intended to promote the establishment of harmony, peace and happiness of living together.